Pembatasan Aktivitas di Luar Rumah pada Lansia di Masa Pandemi Covid-19: Dampak, Strategi Pencegahan dan Koping, Serta Peran Support System - Marpaung, Yosi Marin; Yoan, Margaretha Wulan Puspita (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Older adults are very vulnerable to experiencing various physical, mental and social burdens during the Covid-19 pandemic, one of which is related to changes in life patterns and routines due to restrictions on activities outside the home. The purpose of this research was to identify the impact, prevention and coping strategies, as well as the role of system support for the older people during restrictions on activities outside the home during the Covid-19 pandemic. This research was a cross-sectional study using a non-probability sampling with a questionnaire instrument distributed via Google Form in November 2021. Data analysis was carried out descriptively to see an overview of the data obtained. Of the 51 respondents, activity disturbances were felt in more than 75% of the elderly. The most complained aspect when limiting activities outside the home is felt in mental health (63%) followed by disturbances in physical health (55%) on a moderate to an extensive scale. Respondents could not physically meet with family or relatives and disturbances in religious activities outside the home were the dominant disturbances felt. Furthermore, anxiety was the disorder most frequently reported by respondents, followed by feelings of loneliness and confusion. The family is the main support system for the elderly during social restrictions. An increase in pleasurable physical activity at home needs to be increased during restrictions on outdoor activities. In addition, maintaining the continuity of friendly and safe interaction and communication, increasing access and capacity of communication and information technology, and guaranteeing basic needs and those related to health emergency situations can be key principles for developing older adult-friendly activities during periods of restrictions on activities outside home in the context of future health emergencies. Keywords: Older Adult, Social Restriction, Activity Restriction, Covid-19 Pandemic  ABSTRAK Kelompok lanjut usia adalah kelompok yang sangat rentan mengalami berbagai beban fisik, mental, dan sosial di masa pandemi Covid-19, yang salah satunya berhubungan dengan perubahan pola dan rutinitas kehidupan akibat pembatasan kegiatan di luar rumah. Tujuan dari penelitian ini adalah mengidentifikasi dampak, strategi pencegahan dan koping, serta peran dari dukungan sistem bagi lansia pada masa pembatasan aktivitas di luar rumah di masa pandemi Covid-19. Penelitian ini adalah studi potong lintang menggunakan non-probability sampling dengan instrumen kuesioner dibagikan lewat Google Form di bulan November 2021. Analisis data dilakukan secara deskriptif untuk melihat gambaran data yang diperoleh. Dari 51 responden yang didapatkan, gangguan aktivitas dirasakan pada lebih dari 75% lansia. Aspek yang paling banyak dikeluhkan saat pembatasan aktivitas di luar rumah dengan skala sedang sampai sangat besar dirasakan pada kesehatan mental (63%) diikuti dengan gangguan pada kesehatan fisik (55%). Tidak dapat bertemunya responden dengan sanak saudara atau keluarga dan gangguan pada aktivitas keagamaan di luar rumah menjadi gangguan yang dominan dirasakan. Selanjutnya, kecemasan menjadi gangguan yang paling banyak dilaporkan oleh responden dilanjutkan dengan perasaan kesepian dan bingung. Keluarga menjadi sistem pendukung utama pada lansia di masa pembatasan sosial. Peningkatan aktivitas fisik yang menyenangkan di rumah perlu ditingkatkan pada masa pembatasan aktivitas luar rumah. Selain itu, menjaga kontinuitas interaksi dan komunikasi yang ramah serta aman, peningkatan akses dan kapasitas teknologi komunikasi dan informasi, dan (3) jaminan kebutuhan dasar dan yang berhubungan dengan situasi kedaruratan kesehatan dapat menjadi prinsip kunci pengembangan kegiatan yang ramah pada lansia di masa pembatasan kegiatan di luar rumah, dalam konteks kedaruratan kesehatan di masa depan. Kata Kunci:   Lanjut Usia, Pembatasan Sosial, Pembatasan Aktivitas, Pandemi Covid-19